What factors affect the success rate of the first attempt at endotracheal intubation in emergency departments?. Issue 11 (14th December 2012) - Kim, Changsun; Kang, Hyung Goo; Lim, Tae Ho; Choi, Bo Youl; Shin, Young-jeon; Choi, Hyuk Joong
Abstract : Study objective: This study aimed to determine the factors associated with successful endotracheal intubation (ETI) on the first-attempt in an emergency department. Method: We studied all of the ETI data at two urban emergency departments over a 5-year period. We assessed the intubator's specialty and training level, intubation method, device used, predicted airway difficulty and cause of ETIs. Univariate and multivariate logistic regression models were used to identify factors affecting the first-attempt success (FAS) of ETI in emergency departments. Results: A total of 1478 adult ETIs were analysed. A multivariate logistic analysis revealed that factors such as a non-difficult airway (OR=5.11; 95% CI 3.38 to 7.72), senior physicians (2nd-year to 4th-year resident and attending physicians) (OR=2.39; 95% CI 1.61 to 3.55) and the rapid sequence intubation/induction (RSI) method (OR=2.06; 95% CI 1.04 to 3.03) had significant associations with the FAS for emergency medicine (EM) physicians. For non-EM physicians, however, a non-difficult airway was the only independent predictor of FAS (OR=3.10; 95% CI 1.82 to 5.28). Conclusions: The predicted airway difficulty was the major factor associated with FAS in emergency department ETI on adults regardless of intubator's specialty. Especially in EM physician group, level of training and using of RSI also affecting on first–attempt success. The overall ETI success rate on first attempt was 80.1%, but EM physicians had success rate of 87.3%. Systematic technical and non-technical airway skill training focused on RSI and continuous quality control and ETI recording could help non-EM physicians increase their FAS rate.